PENGARUH FINANCIAL DISTRESS DAN GOOD CORPORATE GOVERNANCE TERHADAP PRAKTIK TAX AVOIDANCE PADA PERUSAHAAN M ANUFAKTUR - Rani Alifianti Herdian Putri; Anis Chariri (Diponegoro Journal of Accounting, 2017)
Taxes are the biggest revenue source of state, so that practice of tax avoidance is strongly discourage by the government. But in fact, there are so many tax avoidance case done by companies that will make state get loss. This study aims to determine the effect of institutional ownership, managerial ownership and audit committee on tax avoidance simultaneously and partially in the automotive subsector listed in the Indonesia Stock Exchange (IDX) 2011-2015. The analytical method that was used are descriptive statistics and multiple linier regression analysis using SPSS. The results showed that financial distress gives positive effect significantly and managerial ownership gives negative effect significantly on tax avoidance. While board of directors give a result as it significantly positive on tax avoidance, hence board of committees and audit committee give negative effect on tax avoidance.